(untitled) (Research, Society and Development, 2025)
As life expectancy increases, the number of people with diseases related to aging increases, with cancer being one of the main causes of death in the world. The diagnosis of cancer causes emotional suffering and impacts the quality of life, altering the patient’s body, appearance and habits. Cancer treatment requires holistic care that includes prevention, diagnosis, treatment, rehabilitation and palliative care. In addition to conventional therapies, unconventional alternatives, such as religiosity and spirituality, have been recognized as helpful, especially in patients undergoing palliative care. Spirituality involves a connection to something greater and a purpose in life, while religiosity refers to religious practice. The objective of the present study is to present a review of the literature which investigates the impacts of spirituality and religiosity on cancer patients. The research used the PICO strategy and was carried out in the PubMed, VHL, Embase, Web of Science and Cochrane databases. After selecting the articles, 15 studies were analyzed, which showed that religiosity and spirituality have a positive impact on quality of life, increasing physical and mental well-being, self-esteem and helping to accept the disease. However, some patients deny spirituality, which can worsen emotional health and increase concern about the disease. Integrating these dimensions into patient care is essential to promote a holistic approach that promotes well-being during treatment.